Transforming space and significance - a study of the constitutional court of South Africa - Rigby, Ursula (School of Architecture, Planning and Geomatics, 2020)
This study examines the process of establishing and building the new South African Constitutional Court as the first intervention in the development of the Constitutional Hill precinct and as part of an endeavour aimed at creating a new national identity. The argument is reliant on the premise that an agency, in this case the judges of the constitutional court, actively seeking out means of transforming space and place and transferring significances in heritage resources, has contributed self-consciously in the process of social transformation. The study is intended to be descriptive of a social reality and explanatory of a special atypical case. Pierre Nora's seminal concept involving lieux de mémoire, their spatial and material potential, and the means by which lieux are formed and retained as lieux (memory objects/vessels/vestiges of heritage) has framed this study. The premise that space and place embodies and transmits concepts of cultural heritage has inspired ongoing and complimentary theories of the ways in which the built environment manifests narratives of power and the role of place in memory. Nora's lieux are social creations often involving built form and it is clear that historically significant built form can be used in social endeavors which contribute to the creation of a society's identity. Research and analysis of the Constitutional Court archive, selected published critique, examination of the artefact itself and by means of interviews with key professional individuals who participated in the programme of the building of the new Constitutional Court, all contribute to an exposure of the process of the endeavour of the judges of the Constitutional Court to establish a “lieux of cultural identity”.